PERANCANGAN ALAT PENCETAK PAVING BLOCK PLASTIK DENGAN PENGGERAK MANUAL - Muhamad Irfan Naufal, (2022)
In its development, plastic waste produced by humans continues to increase. In terms of income, a lot of plastic waste is produced from the remnants of wrappers or containers that are only used once. Reducing plastic waste that is now commonly done is by burning it. This can reduce the amount of plastic waste that exists but the smoke from burning plastic waste is not good for the environment and also human health. Therefore, one way to reduce plastic waste but not harm the environment and humans is to recycle it into new products that can be used. Therefore, it is necessary to make a plastic paving block printer to help reduce plastic waste. So that this thesis takes the theme "Design of Plastic Paving Block Printing Equipment with Manual Drive" which will focus on the process of making the tool. The process of making these tools is based on time, cost, and materials used. In the process of making this machine there are several components that need to be made through the process of machining, welding, painting, and assembling. So that the ﬁnal result of the manufacturing process is obtained the value of time and cost of making plastic paving block printing tools.